2020
DOI: 10.1177/1538574420975908
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Restenosis Following Endarterectomy in Patients Managed With Single Antiplatelet Therapy Versus Dual Antiplatelet Therapy

Abstract: Background: Antiplatelet therapy is a cornerstone in the management of carotid artery disease following carotid endarterectomy (CEA). There is a paucity of data regarding the effect of dual antiplatelet therapy (DAPT) on restenosis rates. Methods: A retrospective review of patients who underwent CEA from January 1, 2007 to December 31, 2013 was performed at a single center. Study groups consisted of subjects who received DAPT and those who received single antiplatelet therapy (SAPT) following CEA. Restenosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Our findings regarding dual antiplatelet therapy in patients with eCEA in lowering the risks of restenosis are similar to those of Glotzer et al 38 and Barboza et al 39 However, the effects of dual antiplatelet therapy on the incidence of carotid restenosis are still to be confirmed in prospective studies, and in the majority of patients, single antiplatelet therapy may be enough.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings regarding dual antiplatelet therapy in patients with eCEA in lowering the risks of restenosis are similar to those of Glotzer et al 38 and Barboza et al 39 However, the effects of dual antiplatelet therapy on the incidence of carotid restenosis are still to be confirmed in prospective studies, and in the majority of patients, single antiplatelet therapy may be enough.…”
Section: Discussionsupporting
confidence: 89%
“…The perioperative and follow-up results revealed that the risk for stroke or death was lower in our patients (1.6 %) than in those without perioperative antiplatelet therapy (2.0 %) in a recent study [ 14 ]. Moreover, consistent with several previous studies, DAPT after surgery was associated with a low risk for postoperative death [ 10 , 24 ]. One patient, 65 years of age, with severe COPD and a history of major stroke died of pulmonary infectious complications that were not associated with the study treatment.…”
Section: Discussionsupporting
confidence: 91%
“…A small, single-site study of 44 patients showed no increase in bleeding and less 30-day restenosis rates 29. Another single-centre larger study also found that DAPT was associated with lower rates of restenosis when compared with SAPT but this did not translate to any difference in reintervention rate 30. Our findings raise important questions into whether, after appropriate clinical re-evaluation, more patients could have been downgraded from preprocedure DAPT and the appropriateness of such a significant number of participants on SAPT being upgraded to DAPT.…”
Section: Discussionmentioning
confidence: 61%
“…29 Another single-centre larger study also found that DAPT was associated with lower rates of restenosis when compared with SAPT but this did not translate to any difference in reintervention rate. 30 Our findings raise important questions into whether, after appropriate clinical re-evaluation, more patients could have been downgraded from preprocedure DAPT and the appropriateness of such a significant number of participants on SAPT being upgraded to DAPT. Future studies need to determine how different discharge APT regimens (single vs double) and changes in APT regiments (both upgrade and downgrade) impact outcomes.…”
Section: Discussionmentioning
confidence: 86%